Plasmodium falciparum field isolates from areas of repeated emergence of drug resistant malaria show no evidence of hypermutator phenotype. - Brown, T; Jacob, C; Silva, J; Takala-Harrison, S; Djimdé, A; Dondorp, A; Fukuda, M; Noedl, H; Nyunt, M; Kyaw, M; Mayxay, M; Hien, T; et al. (2014)
Multiple transcontinental waves of drug resistance in Plasmodium falciparum have originated in Southeast Asia before spreading westward, first into the rest of Asia and then to sub-Saharan Africa. In vitro studies have suggested that hypermutator P. falciparum parasites may exist in Southeast Asia and that an increased rate of acquisition of new mutations in these parasites may explain the repeated emergence of drug resistance in Southeast Asia. This study is the first to test the hypermutator hypothesis using field isolates. Using genome-wide SNP data from human P. falciparum infections in Southeast Asia and West Africa and a test for relative rate differences we found no evidence of increased relative substitution rates in P. falciparum isolates from Southeast Asia. Instead, we found significantly increased substitution rates in Mali and Bangladesh populations relative to those in populations from Southeast Asia. Additionally we found no association between increased relative substitution rates and parasite clearance following treatment with artemisinin derivatives.